Functional Outcome of Proximal Femoral Nailing in Intertrochanteric Fracture - Thakur, Prashant; Khanal, Krishna Raj; Amatya, Isha (Journal of Nepal Health Research Council, 2022)
Background: Intertrochanteric fracture of femur is one of the commonest fracture seen in elderly, osteoporotic female. The main stay of treatment is fixation with dynamic hip screw or intramedullary device like Proximal Femoral Nail. Intramedullary devices are found to be more biomechanically advantageous. The functional outcome of these fractures depends on the type of fixation, age and stability of fracture. The objective of this study is to assess the functional outcome of Proximal Femoral Nail in intertrochanteric fracture. Methods: An observational study was conducted in Kathmandu Medical College, Sinamangal from January 2018 to May 2019. 32 patients with intertrochanteric fracture were treated with proximal femoral nail during this period. The functional outcome was measured at 6 weeks, 12 weeks and 6 months using Harris hip score. Results: There were 46.9% males and 53.1% females with mean age of 71.09 ±12.35 years. Most of the patients sustained injury after falling from standing height (53.1%). The functional outcome measured at final follow up (6 months) with Harris hip score was good in 62.5% and excellent in 28.1% patients likewise follow up in 12 weeks was good in 15.6%. Conclusions: Proximal Femoral Nail in trochanteric fractures seem to provide a good functional outcome at 6 months follow up. This technique, therefore appears to be a viable option in the management of intertrochanteric fracture of femur. Keywords: Harris hip score; Intertrochanteric fracture; proximal femoral nail.